Between Yesterday and Tomorrow German Visions of Europe, 1926-1950 - Bailey, Christian (Berghahn Books, 2013)
An intellectual and cultural history of mid-twentieth century plans for European integration, this book calls into question the usual pre- and post-war periodizations that have structured approaches to twentieth-century European history. It focuses not simply on the ideas of leading politicians but analyses debates about Europe in "civil society" and the party-political sphere in Germany, asking if, and how, a "permissive consensus" was formed around the issue of integration. Taking Germany as its case study, the book offers context to the post-war debates, analysing the continuities that existed between interwar and post-war plans for European integration. It draws attention to the abiding scepticism of democracy displayed by many advocates of integration, indeed suggesting that groups across the ideological spectrum converged around support for European integration as a way of constraining the practice of democracy within nation-states